Hardcore, Punk, and Other Junk: Aggressive Sounds in Contemporary Music - Abbey, Eric James; Helb, Colin (Lexington Books, 2014)
Hardcore, Punk, and Other Junk: Aggressive Sounds in Contemporary Music, edited by Eric James Abbey and Colin Helb,is a collection of writings on music that is considered aggressive throughout the world. From local underground bands in Detroit, Michigan to bands in Puerto Rico or across Europe, this book demonstrates the importance of aggressive music in our society. While other volumes seek to denigrate or put down this type of music, Hardcore, Punk, and Other Junk forces the audience to re-read and re-listen to it. This category of music includes all forms that could be considered offensive and/or move the audience to become aggressive in some way. The politics and values of punk are discussed alongside the emerging popularity of metal and extreme hardcore music. Hardcore, Punk, and Other Junk is an important contribution to the newest discussions on aggressive music throughout the world.